Investing in Sub-Saharan African agricultural research: Recent trends - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2004)
Agricultural research capacity is an important factor in building food security and economic stability in Africa. Furthermore, new and better-targeted technologies are essential to this process, and a well-developed and wellsupported agricultural research system is a prerequisite not only for the design of these technologies but also for their dissemination and adoption...In view of the low, and often declining, level of agricultural R&D investments in SSA, both in real terms and as a ratio of agricultural output, attaining this goal will be extremely challenging. -- from Text